Improving the Ability of the 6th Grade Students at SDN Petemon X/358 Surabaya to Write Descriptive Texts Using Four-Square Technique - Musafa'ah, Ani (English Language and Literature in Education Journal, 2023)
The purpose of this research was to increase students' achievement in writing descriptive text by implementing the Four-Square Writing Technique (FSWT) to the 6th grade students at SDN Petemon X/358 Surabaya in the academic year 2020/2021. Each cycle of classroom action research consisted of three meetings and included four steps: planning, action, observation, and reflection. The data were gathered through the use of two instruments: observation and test. The results indicated that students made great progress in their ability to write descriptive texts. Pre-test mean score was only 62.42, but improved to 71.10 in cycle I and 77.30 in cycle II. The pre-test score was only 74 and improved to 82 to 88 in subsequent cycles. Meanwhile, the lowest pre-test score was 50, and the highest post-test score ranged from 62 to 68. In case of the students who passed the tests, while only five students (16.67%) passed the pre-test, there were significant improvements in post-tests, with 18 students (60%) passing in post-test cycle I and 27 students (90%) passing in post-test cycle II. This research was stopped in cycle II due to the fact that the criteria for success were met in a percentage of 90%, with 27 students passing the post-test in cycle II, based on the Minimum Mastery Criteria (KKM) standard of > 70.